Potential Application of Bioactive Gambir Gum as a Next-Gen Oral Care Product: An In Vitro Study on Streptococcus mutans Reduction and Salivary pH Modulation - Navila Samsa Volasoohy; M. Rofif Azzuchri; Mutia Erliza Mashfufah; Davin Abrar; M. Zidan Rosyadi; Zuhrah Taufiqa (CV. AFDIFAL MAJU BERKAH, 2026)
Dental caries is the most prevalent oral health problem in Indonesia. Caries occurs due to bacterial colonization, primarily by Streptococcus mutans. Prevention of dental caries can be achieved by utilizing gambier (Uncaria gambier, Roxb) as an antimicrobial agent in the form of chewing gum combined with xylitol. This study aimed to develop an innovative bioactive formulation of gambier gum and to determine its effectiveness in reducing Streptococcus mutans colony counts and increasing salivary pH, both of which play roles in improving oral health and hygiene. This experimental study was conducted at the Biomedical Laboratory, Faculty of Medicine, Universitas Negeri Padang, from July to October 2025. Three formulations of gambier gum containing catechin concentrations of 0%, 70%, and 95% were tested for effectiveness by mixing them with participants’ saliva samples. The results showed a reduction in Streptococcus mutans colony counts compared to the control. Culture results of gambier gum with 0%, 70%, and 95% catechin demonstrated reductions of 40%, 60%, and 100%, respectively, relative to the control colonies. pH measurements indicated that gambier gum with 95% catechin prevented the saliva from becoming acidic. The gambier gum formulation containing 95% catechin exhibited the greatest antimicrobial effectiveness.